The Effect of Corporate Governance on Profit Management - Michal Wasserbauer (Greenation International Journal of Tourism and Management, 2023)
This study aims to determine the effect of corporate governance as measured by an independent board of commissioners, board size of managerial ownership and board diversity on earnings management . The collection used the purposive sampling method so that a total of 58 JII and NON JII companies were obtained for the 2014-2017 period. The data analysis technique used in this study was a quantitative method, then the data was classified into certain categories and with certain tables, in this study using the application STATA 12 . The results of this study indicate that there are factors that can predict the occurrence of earnings management in a company with an independent board of commissioners, board size, managerial ownership, and board diversity in both companies listed on JII and non-JII.